2020
DOI: 10.3390/ma13071769
|View full text |Cite
|
Sign up to set email alerts
|

Use of ZnAl-Layered Double Hydroxide (LDH) to Extend the Service Life of Reinforced Concrete

Abstract: This work investigated the use of ZnAl-layered double hydroxide (LDH) intercalated with nitrate or nitrite ions for controlling the corrosion of steel in reinforced concrete. The work started by analyzing the stability of the powder in the 1-14 pH range and the capacity for capturing chloride ions in aqueous solutions of different pH. The effect of the ZnAl-LDH on the corrosion of steel was studied in aqueous 0.05 M NaCl solution and in mortars immersed in 3.5% NaCl. It was found that the LDH powders dissolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 63 publications
0
12
1
Order By: Relevance
“…On the other hand, LDH can also decelerate or retard cement hydration. Recent studies by Gomes et al [25] reveled that addition of ZnAl LDH had a decelerating effect on hydration processes and early strength development. They used a dosage of 2-5% LDH to cement with an average particle size of 25 µm in cement pastes.…”
Section: Effect On Hydrationmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, LDH can also decelerate or retard cement hydration. Recent studies by Gomes et al [25] reveled that addition of ZnAl LDH had a decelerating effect on hydration processes and early strength development. They used a dosage of 2-5% LDH to cement with an average particle size of 25 µm in cement pastes.…”
Section: Effect On Hydrationmentioning
confidence: 99%
“…The presence of Zn 2+ ions in the early stages of cement hydration can lead to formation of Zn-Ca complexes such as Ca(Zn(OH 3 ) 2 )·2H 2 O which in turn reduce the concentration of Ca 2+ and OH − in the pore solution thereby retarding the hydration reactions [114]. Gomes et al [25] also observed that particle size matters because bigger agglomerates ∼125 µm did not affect the hydration. This can be understood considering the reduced surface area of bigger agglomerates which do not suffer so significant dissolution as compared to finer particles.…”
Section: Effect On Hydrationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the capacity to capture chloride ions can be influenced by the amount of LDH itself as well as pH of the surrounding environment. [52] The chloride capture is very fast and a thermodynamic heterogeneous equilibrium is established almost instantly.…”
Section: Mg-al-no 2 Efficiency Toward Additional Chloride Bindingmentioning
confidence: 99%